Assessment of soil degradation potency for biomass production and the strategy for its management in Giriwoyo-Indonesia. Issue 1 (1st February 2022) - Mujiyo; Hardian, T; Widijanto, H; Herawati, A
Abstract: Biomass production supports humans need for food so needs to be supported by optimal soil conditions. The study related to the potential for soil degradation in land characteristics is the first step for sustainable agricultural control. Potential soil degradation is compiled from the number of scores for each land map unit (soil type, slope, rainfall, land use) using technical guidelines for the preparation of soil degradation, and the Pearson correlation test to examine the causal relationship of soil degradation from each land characteristic. The results show that the land with the highest potential is with moderate level potential of 4, 671.83 hectares (46.44% area) and the other part of 3, 953.13 hectares (39.30% area) has low potential level. The main factors for potential soil degradation are the slopes, rainfall, and land use. The steeper the slopes and the high rainfall carried out on intensive agricultural land, the greater the degradation to the soil. Suggested land management strategies include soil conservation with minimal tillage, mulch application, terrace construction, and planting parallel to the soil contour. In addition, erosion research needs to be carried out to determine in detail the magnitude of the erosion prediction in this area.